2001
DOI: 10.1042/bj3580095
|View full text |Cite
|
Sign up to set email alerts
|

A maize insulin-like growth factor signals to a transduction pathway that regulates protein synthesis in maize

Abstract: Insulin and insulin-like growth factors (IGFs) are well-characterized regulators in higher eukaryotic cells that control biological processes such as cell growth and survival, and selective translation of mRNAs. This research presents the purification of a 20kDa protein, isolated from maize tissue, with IGF activity. The protein was purified from 48h-germinated maize embryonic axes by G-50 Sephadex fractionation followed by affinity chromatography through a bovine insulin antibody–Sepharose column. This protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…For most eukaryotes, a signal transduction pathway known as the TOR-S6K pathway, activated by insulin or insulin-like peptides, is responsible for regulating growth and (r)-protein synthesis at the translational level (Hay andSonenberg 2004, Holdsworth et al 2008). Experimental evidence has demonstrated that this TOR-S6K pathway is highly conserved in plants (Robaglia et al 2004) and particularly in maize (Reyes de la Cruz et al 2004, Agredano-Moreno et al 2007 as is its sensitivity to insulin stimuli (García-Flores et al 2001, Dinkova et al 2007, providing a basic framework for the interpretation of the microarray analysis data in the present research. Indeed, application of insulin or ZmIGF, the maize insulin-like growth factor (Rodríguez-López et al 2011), to the axes stimulates (r)-protein synthesis (Fig.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…For most eukaryotes, a signal transduction pathway known as the TOR-S6K pathway, activated by insulin or insulin-like peptides, is responsible for regulating growth and (r)-protein synthesis at the translational level (Hay andSonenberg 2004, Holdsworth et al 2008). Experimental evidence has demonstrated that this TOR-S6K pathway is highly conserved in plants (Robaglia et al 2004) and particularly in maize (Reyes de la Cruz et al 2004, Agredano-Moreno et al 2007 as is its sensitivity to insulin stimuli (García-Flores et al 2001, Dinkova et al 2007, providing a basic framework for the interpretation of the microarray analysis data in the present research. Indeed, application of insulin or ZmIGF, the maize insulin-like growth factor (Rodríguez-López et al 2011), to the axes stimulates (r)-protein synthesis (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Further, analysis of the regulation of expression related to ribosomal protein [(r)-protein] mRNAs was pursued, considering that expression of these genes constitutes the platform for the embryo to grow and develop. Previous reports demonstrated that insulin or insulin-like growth factors are able to stimulate growth in most eukaryotes (Fingar andBlenis 2004, Leevers andHafen 2004), including several plant species during seed germination (Goodman and Davis 1993, García-Flores et al 2001, Oliveira et al 2004). Furthermore, accelerated (r)-protein synthesis has been found following either insulin or maize insulin-like growth factor (ZmIGF; Rodríguez-López et al 2011) stimulation, in germinating maize seeds (García-Flores et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, analysis of the regulation of expression related to ribosomal protein [(r)-protein] mRNAs was pursued, considering that expression of these genes constitutes the platform for the embryo to grow and develop. Previous reports demonstrated that insulin or insulin-like growth factors are able to stimulate growth in most eukaryotes (Fingar andBlenis 2004, Leevers andHafen 2004), including several plant species during seed germination (Goodman and Davis 1993, García-Flores et al 2001, Oliveira et al 2004. Furthermore, accelerated (r)-protein synthesis has been found following either insulin or maize insulin-like growth factor (ZmIGF; Rodríguez-López et al 2011) stimulation, in germinating maize seeds (García-Flores et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Seed tissues have different functions during germination, and in maize this period lasts approximately 24 h (García-Flores et al 2001). It has been documented that the endosperm of grains such as maize or barley degrades mRNAs early in germination, whereas within the scutellum and embryonic axis, translation is reinitiated based on the stored mRNAs (Holdsworth et al 2008).…”
Section: Introductionmentioning
confidence: 99%